Maximizing separation performance of q-cascades for multicomponent isotope separation. Issue 1 (2nd January 2018) - Zeng, Shi; Zhang, Yunan; Jiang, Dongjun; Borisevich, Valentin; Sulaberidze, Georgy; Smirnov, Andrei
ABSTRACT: The Q-cascade is a type of model cascade that is particularly useful for studying multicomponent isotope separation. The cascade segmentation technique is further developed to optimize Q-cascades, which minimizes the relative total flow by splitting a cascade into smaller segments that each use the mass number of the virtual component as a decision variable. Application of this technique to Cadmium isotope separation shows that it is always effective. If the number of segments into which a cascade is split increases, then the minimum relative total flow decreases. A progressive segmentation strategy is developed to maximize the number of segments.